Effect Of Combination Hormone hCG (Human Chorionic Gonadotropin) With Ovaprim To Ovulation And Hatching Rate Of Signal Barb (Labeobarbus festivus, Heckel 1843) - Ady Putra Raja gukguk; Sukendi Sukendi; Netti Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT The research was conducted from August to October 2019 in the Laboratory of Fish Hatchery and Breeding (PPI), Faculty of Fisheries and Marine Science, University of Riau. The purpose of this research is to know the effect of hCG combination with ovaprim to ovulation and egg hatchability Mali fish (Labeobarbus festivus, Heckel 1843) and to know of hCG with ovaprim best treatment to stimulate ovulation and hatching rate eggs ofSignal Barb(Labeobarbus festivus, Heckel 1843). This study uses a completely randomized design (CRD) with four treatments where each treatment was made in three replications. Dose of hormones used are treatment 1: hCG 0 IU / kg + ovaprim 0,5ml / kg of body weight (control), treatment 2: hCG 350 IU / kg + ovaprim 0,5ml / kg of body weight, treatment 3: hCG 450 IU / kg + ovaprim 0,5ml / kg of body weight, treatment 4: hCG 550 IU / kg + ovaprim 0,5ml / kg of body weight. The results showed that the best treatment was found in P4 (hCG 550 IU / kg + Ovaprim 0.5 ml / kg)produce latency time for 5 hours 18 minutes, the number of eggs stripping as many as 299 eggs / grbroodstock, egg diameter of 0.926 mm, egg maturity of 88.8%, ovisomatic index value of 15.73%, fertilization rate 76.93%,hatching rate 80.23%, and survival rate (SR5) amounted to 80.25%.Results of water quality measurements during the study is 27-31oC temperature and pH 5-7.Keywords: Signal barb, hCG, ovaprim, latency time, diameter eggs, egg maturity, fertilization rate, hatching rate, survival rate